Tanggung Jawab Pelaku Usaha Obat Herbal Atas Pencantuman Nomor Izin Edar Fiktif - Bayu Sapto Aji; Merry Tjoanda; Sarah Selfina Kuahaty (TATOHI: Jurnal Ilmu Hukum, 2022)
Introduction: Health is an important element in human life. One of the factors that support health is the drug used.Purposes of the Research: The purpose of this study is to find out and explain the responsibility of herbal medicine business actors for the inclusion of a fictitious distribution permit number in Ambon CityMethods of the Research: The method used in this research is a normative juridical method with a statutory approach and a conceptual approach. The legal materials used are primary, secondary and tertiary legal materials. The legal material is analyzed qualitatively in order to answer the problems studied.Result of the Research: As a result of the actions of business actors who unlawfully cause harm to consumers by including fictitious NIE on herbal medicinal products, business actors must be responsible based on the principle of error. Because of the bad faith mistake of the business actor who intentionally includes a fictitious NIE to obtain the maximum profit, the consumer will be greatly harmed when consuming the herbal medicinal product. Violations committed by these business actors need to get the attention of the government through the Food and Drug Supervisory Agency with the supervisory function carried out. Ambon City BPOM in carrying out its supervisory function related to the circulation of herbal medicines with the fictitious NIE has been intensively carried out in collaboration with other relevant agencies so that violations by herbal medicine business actors are still found in Ambon City.